RESPON INVESTOR TERHADAP PENGUMUMAN LABA INDUSTRI PERBANKAN YANG MENGHADAPI KOS STICKINESS - Windyastuti Windyastuti; Kunti Sunaryo; Sri Hastuti (Jurnal Keuangan dan Perbankan, 2017)
This study aimed to analyze the response of investors to the announcement of the financial statements of the banking sector. The population in this study was the banking industry. This study used purposive sampling method. Based on sampling techniques the number of samples in this study was 11 banks. The research period was 2002-2014. The analysis technique used was panel data regression. The result showed that investor response to the financial statements of banks which faced cost stickiness was weak. The increase of cost stickiness on the banking sector led the weak investor response to the announcement of the financial statements of banks. In the banking companies facing cost stickiness problem, earnings prediction accuracy reduced. This causes the income statement would provide information that was less important to the earnings prediction in the next periods.